Incidence and risk factors for early neonatal mortality in newborns with severe perinatal morbidity in Uganda. Issue 2 (8th July 2014) - Musooko, Moses; Kakaire, Othman; Nakimuli, Annettee; Nakubulwa, Sarah; Nankunda, Jolly; Osinde, Michael O.; Mbalinda, Scovia N.; Kakande, Nelson; Kaye, Dan K.
Abstract: Objective: To determine the incidence and risk factors for early neonatal death among newborns with severe perinatal morbidity. Methods: A prospective cohort study was performed of 341 newborns with severe perinatal morbidity admitted to the neonatal intensive care unit of Mulago Hospital, Uganda. All newborns were followed up for 7 days or until time of death. Information surrounding the mother's obstetric history and pregnancy, the birth, and the neonatal history was collected using an interviewer‐administered questionnaire and by review of relevant records. Multivariate logistic regression analysis was performed to assess factors independently associated with early neonatal death. Results: A total of 37 (10.9%) neonates died within 7 days, giving an incidence of early neonatal death of 109 deaths per 1000 live births (3 per 100 person‐days). In multivariate analysis, respiratory distress (adjusted risk ratio [aRR] 31.29; 95% CI, 4.17–234.20; P = 0.001) and inadequate fetal heart monitoring during labor (aRR 6.0; 95% CI 1.40–25.67; P = 0.016) were significantly associated with an increased risk of early neonatal death. Conclusion: Approximately one in 10 neonates with severe perinatal morbidity died within 7 days of birth. Respiratory distress and poor monitoring of labor were risk factors for early neonatal death.